Dampak Kepemimpinan Transformasional Kepala Sekolah Terhadap Kinerja Guru di Era Digital (Studi Kualitatif di SMP Negeri 3 Cikampek) - Nia Kaniati; Agus Virgo; Suharyanto Soro; Dinny Mardiana (Civiliza Publishing, Indonesia., 2025)
There is still limited research that examines in depth the implementation of transformational leadership of school principals and their impact on teacher performance in the digital era, especially at the junior high school level. The transformation of education in the digital era requires the active role of school principals in encouraging the improvement of teacher performance in an adaptive and sustainable manner. This study aims to find and analyze the transformational leadership of school principals in improving teacher performance in the digital era. This research uses a qualitative approach with a descriptive analysis method. The data collection method was carried out through observation, in-depth interviews, and documentation studies. Samples are selected based on purposive sampling. The selected samples were school principals, teachers based on education level and class rank, students based on roles in school organizations. Data analysis is done through the stages of data reduction, data presentation, and conclusion drawn, with data validity tests using triangulation of sources, techniques, and time. The results of the study show that (1.) school principals have applied transformational leadership principles through the involvement of teachers in deliberation and decision-making as well as encouragement for digital learning adaptation; (2) the implementation of leadership has not been completely consistent, especially related to sudden policy changes and lack of adequate socialization; (3) Leadership has an impact on teacher performance, especially in the planning and implementation of digital learning, and affects the stability of teachers' motivation and work effectiveness. Conclusion: transformational leadership of school principals has great potential in improving teacher performance in the digital era, but its effectiveness is largely determined by policy consistency, clarity of communication, and attention to individual teacher needs. These findings provide theoretical and practical contributions to the development of leadership of school principals that are adaptive to the challenges of educational digital transformation.